SISTEM INFORMASI AKUNTANSI PENERIMAAN KAS PADA PENDAPATAN JASA RAWAT INAP PADA RUMAH SAKIT PRIMA MEDIKA KOTA DENPASAR BALI - Sofyan Noor (Journal Accounting International Mount Hope, 2024)
The importance of managing information systems in the face of rapid change and intense competition cannot be denied. Prima Medika Hospital in Denpasar City understands the importance of a cash receipt accounting information system to manage financial information effectively. With a structured system, hospitals can ensure that the income reports produced are accurate, relevant and trustworthy. This contributes to better decision making and optimal strategic planning. This study was designed to examine the financial information system, especially the cash receipt process which is applied to manage income from inpatient services at Prima Medika Hospital. The goal is to gain a deeper understanding of the procedures and effectiveness of the system in the context of hospital finances. The results show that the cash receipt accounting system in the hospital's inpatient installation is quite good and in accordance with the existing system.